1975
DOI: 10.1017/s0081305200012176
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Major Crop Acreage Response

Abstract: In recent years, several studies have examined acreage response of major crops to various economic, technical, and institutional stimuli. These studies focused primarily upon the influence of government farm programs on producers' production decisions. While the influence of government programs has recently diminished and market forces are more direct determinants, this less stable situation has likely increased informational needs on potential production response. Previously developed response models require … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1985
1985
1985
1985

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Mann, 1973;Meyers and Hacklander, 1979;R. Miller, 1979;Neenan, 1981;Penn and Irwin, 1971;Rao, 1965;Ray, 1971;Ray and Heady, 1974;Reed and Rigglns, 1981;Reynolds, Heady, and Mltchel, 1975;Salathe, Price, and Gadson, 1982;Schatzer, Roberts, and Heady, 1981;Walker and Penn, 1975;Whittaker and Bancroft, 1979;Winter and Whittaker, 1979). Despite its frequent use, the adaptive expectations model is criticized for the lack of a theoretical basis for the geo metrically declining lag structure (Grillches, 1967;Lin, 1977), the assumed constancy of the coefficient of expectation 3, and the neglect of current price information (Lin, 1977 tfc f where p^ is the expected price, p^ ^ is the actual farm price, p^ is the effective support price, and w^, w^ are weights, with w^ + = 1.…”
Section: =1mentioning
confidence: 99%
See 2 more Smart Citations
“…Mann, 1973;Meyers and Hacklander, 1979;R. Miller, 1979;Neenan, 1981;Penn and Irwin, 1971;Rao, 1965;Ray, 1971;Ray and Heady, 1974;Reed and Rigglns, 1981;Reynolds, Heady, and Mltchel, 1975;Salathe, Price, and Gadson, 1982;Schatzer, Roberts, and Heady, 1981;Walker and Penn, 1975;Whittaker and Bancroft, 1979;Winter and Whittaker, 1979). Despite its frequent use, the adaptive expectations model is criticized for the lack of a theoretical basis for the geo metrically declining lag structure (Grillches, 1967;Lin, 1977), the assumed constancy of the coefficient of expectation 3, and the neglect of current price information (Lin, 1977 tfc f where p^ is the expected price, p^ ^ is the actual farm price, p^ is the effective support price, and w^, w^ are weights, with w^ + = 1.…”
Section: =1mentioning
confidence: 99%
“…Various authors have found some form of the weighted support price technique to be relatively successful in tracking actual crop acreage re sponse over time (Evans and Kenyon, 1974;Gallagher, 1978;Grant and Leath, 1979;Houck and Subotnik, .1969;Ryan andAbel, 1973a, 1973b;Walker and Penn, 1975). Danin (1976) questions the theoretical basis for the effective price variables and suggests additional investigation is needed to explain the "success" in the empirical studies.…”
Section: =1mentioning
confidence: 99%
See 1 more Smart Citation
“…Mann, 1973;Meyers and Hacklander, 1979;R. Miller, 1979;Neenan, 1981;Penn and Irwin, 1971;Rao, 1965;Ray, 1971;Ray and Heady, 1974;Reed and Rigglns, 1981;Reynolds, Heady, and Mltchel, 1975;Salathe, Price, and Gadson, 1982;Schatzer, Roberts, and Heady, 1981;Walker and Penn, 1975;Whittaker and Bancroft, 1979;Winter and Whittaker, 1979). Despite its frequent use, the adaptive expectations model is criticized for the lack of a theoretical basis for the geo metrically declining lag structure (Grillches, 1967;Lin, 1977), the assumed constancy of the coefficient of expectation 3, and the neglect of current price information (Lin, 1977).…”
Section: =1mentioning
confidence: 99%
“…A third technique for measuring the impact of government programs upon acreage response is Houck and Subotnik's (1969) (Gallagher, 1978;Houck and Subotnik, 1969;Lin, 1977;Ryan andAbel, 1973a, 1973b;Walker and Penn, 1975;Whittaker and Bancroft, 1979;Winter and Whittaker, 1979); however, it is criti cized on grounds that participation in an acreage diversion program is treated as an exogenous variable when, in fact, it is more appropriately treated as endogenous (Bancroft, 1981). An argument is made that the extent of diversion is a function of market prices relative to the in centives to participate in commodity programs (i.e., support payments, loan rates, and diversion payment rates).…”
Section: Impact Of Government Program Variablesmentioning
confidence: 99%